An evaluation of the use of the Universal Benefit–Risk Assessment Framework by the Zambia Medicines Regulatory Authority for documenting and communicating benefit–risk decisions - Constance Sakala Chisha; Stephanie Leigh; Prudence Musonda Mubanga; Bernice Mumbi Chilufya; Makomani Siyanga; Stuart Walker (Regulatory Toxicology and Pharmacology, 2026)

Evaluating a structured expert elicitation approach for adaptive conservation management based on lessons from five years in practice - Helen J. Mayfield; James Brazill‐Boast; Mick Andren; Michiala Bowen; Adam Fawcett; Trent Forge; Luke Foster; Ross Goldingay; Paul Hillier; Meagan Hinds; Simon Lee; Erica Mahon; et al. (Conservation Biology, 2026)
Adaptive management of threatened species relies on having ex ante estimates of species’ responses to different interventions. Structured expert elicitation is often used to generate these estimates, but comparisons of these expert‐predicted outcomes with observed results are rare. This study aims to evaluate the utility of expert elicitation for adaptive management in the New South Wales Saving our Species program in Australia by revisiting six species management plans that were generated from tailored structured elicitation guidelines developed five years prior. Each species’ management plan included a defined scope, conceptual model, monitoring indicators, and estimated response to management curves under different scenarios. Experts reviewed the conceptual models after five years of management and compared the predicted response to management with observed monitoring data. In three of the six case studies, observed outcomes closely matched predictions. Where predictions diverged, factors such as unanticipated new threats and unexpected responses to interventions potentially contributed to discrepancies. However, in all cases, the structured approach provided a clear logic for planning, enabling managers to systematically refine their understanding. The conceptual models and response curves were valuable for collaborating, communicating, and generating hypotheses for unexpected results. This work demonstrates the value of tailored guidelines in supporting adaptive management processes and showcases the value of documenting expert knowledge in management settings with high uncertainty.

Camizestrant-induced heart rate reduction is mediated via a sinoatrial node pacemaker channel mechanism - Andrew Hall; Saïd El-Haou; Inmaculada C. Villar; David Molla; Maggie Kwan; Stuart Purbrick; David Henry; Jason Kirk; Glen Hawthorne; Serena Canzolino; Joanna Harding; Alexander Harmer; et al. (Toxicology and Applied Pharmacology, 2026)

Twenty-four-hour blood pressure and CSF biomarkers of Alzheimer’s disease and related dementias in a community cohort - Madeline Gibson; William T. O’Brien; Ella Rowsthorn; Katherine H. Franks; Lachlan Cribb; Marina Cavuoto; Beaudan Campbell-Brown; Ian Harding; Meng Law; Trevor T.-J. Chong; Stuart J. McDonald; Terence J. O’Brien; et al. (GeroScience, 2026)
Hypertension in midlife is associated with increased dementia risk, yet its relationship with early pathological changes of Alzheimer’s disease and related dementias (ADRD) remains unclear. Unlike office blood pressure (BP), 24-h ambulatory BP (ABPM) may better reflect cardiovascular risk, but associations between 24-h BP measures with ADRD biomarkers are unknown. This cross-sectional study examined associations between BP and cerebrospinal fluid biomarkers of ADRD in mid-to-late life. Dementia-free participants ( n = 77; mean age = 67 [SD, 6]; 39% women) from the community-based Brain and Cognitive Health (BACH) cohort underwent office and 24-h ABPM assessments to calculate mean BP, nocturnal dipping, blood pressure variability (BPV, coefficient of variation) across 24-h, awake and asleep periods. Participants also completed a lumbar puncture to assess ADRD biomarkers: Aβ42/Aβ40 ratio, phosphorylated tau at threonine 217 (pTau217), glial fibrillary acidic protein (GFAP), and neurofilament light chain (NfL). Linear regression models examined associations between BP and ADRD biomarkers, adjusting for age, sex, BMI, smoking, anti-hypertensive medication use, and APOE ε4 status. Higher 24-h and awake mean BP were associated with higher GFAP (24-h: per 1-SD unit increase, β = 1606.6 pg/mL, p = .03; awake: β = 1668.pg/mL, p = .03) and NfL (24-h: β = 172.3 pg/mL, p = .03; awake: β = 162.3 pg/mL, p = .04) levels. Elevated asleep BPV was associated with higher Aβ42/Aβ40 ratio ( β = 0.01, p = .01). No, other clear associations were identified for the other BP metrics ( p > .05 for all). Findings indicate that elevated BP is associated with neuronal injury and astrocytic reactivity, suggesting possible pathways through which BP may relate to neurodegenerative processes, independent of overt amyloid or tau.

Factor analysis of multimodal MRI, biofluid, and vascular biomarkers reveals latent constructs of brain health - Ella Rowsthorn; Ming Ann Sim; William T. O’Brien; Stuart J. McDonald; Katherine Franks; Benjamin Sinclair; Trevor T.-J. Chong; Stephanie Yiallourou; Marina Cavuoto; Lucy Vivash; Terence J. O’Brien; Xingfeng Shao; et al. (GeroScience, 2025)
Individual imaging and fluid biomarkers provide insights into specific components of brain health, but integrated multimodal approaches are necessary to capture the complex, interrelated biological systems that contribute to brain homeostasis and neurodegenerative disease. Using data from the Brain and Cognitive Health (BACH) cohort study ( N = 127; mean age = 67 years, 68% women), we performed an exploratory factor analysis to identify latent constructs of brain health. We included multimodal neurovascular imaging markers, brain atrophy metrics, plasma Alzheimer’s disease (AD) biomarkers, and cardiovascular risk factors. Five constructs emerged: “Brain & Vascular Health” (greater hippocampal volume, basal ganglia enlarged perivascular spaces (ePVS), cerebral blood flow, and HDL cholesterol; lower ventricle volume and BMI), “Structural Integrity” (greater cortical thickness, fractional anisotropy, and basal ganglia ePVS), “White Matter (WM) Fluid Dysregulation” (greater WM ePVS and Free Water), “AD Biomarkers” (higher phosphorylated tau [pTau]181 and pTau217; lower amyloid-beta 42/40 ratio), and “Neuronal Injury” (higher glial fibrillary acidic protein and neurofilament light chain). All constructs were associated with age (β = - 0.70–0.39, p ≤ 0.014), except for WM Fluid Dysregulation ( p > 0.05). Brain and Vascular Health and Structural Integrity (partial r = 0.305, p < 0.001) and AD biomarkers and neuronal injury (partial r = 0.248, p = 0.005) were positively correlated. Only Brain and Vascular Health was associated with global cognition (β = 0.27, SE = 0.13, p = 0.043). These findings provide a data-driven framework for examining distinct constructs underlying vascular health, fluid regulation, and neurodegenerative pathology. We demonstrate the utility of using multiple biomarkers to probe these biological systems, paving the way for future research to explore how these systems change across diverse neurodegenerative conditions. Graphical abstract

Correction to: Biogeophysical drivers of abundance for habitat-shifting reef fishes on stepping-stone coral patch reefs - Sofia W. S. Panzetta; Courtney E. Stuart; Stephanie J. Green (Coral Reefs, 2025)

Biogeophysical drivers of abundance for habitat-shifting reef fishes on stepping-stone coral patch reefs - Sofia W. S. Panzetta; Courtney E. Stuart; Stephanie J. Green (Coral Reefs, 2025)

The potential for AI to revolutionize conservation: a horizon scan - Sam A. Reynolds; Sara Beery; Neil Burgess; Mark Burgman; Stuart H.M. Butchart; Steven J. Cooke; David Coomes; Finn Danielsen; Enrico Di Minin; América Paz Durán; Francis Gassert; Amy Hinsley; et al. (Trends in Ecology & Evolution, 2025)

Alternative domestic rodent pest management approaches to address the hazardous use of metal phosphides in low- and middle-income countries - Alexander M. Stuart; Jens Jacob; Adedayo Michael Awoniyi; Federico Costa; Luwieke Bosma; Yonas Meheretu; Nyo Me Htwe; Stephanie Williamson; Michael Eddleston; Ambroise Dalecky; Sheila Willis (Journal of Pest Science, 2025)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

Forecasting a Summer of Extremes: Building Stakeholder Response Capacity to Marine Heatwaves - Alistair Hobday; Claire Spillman; Jamie Allnutt; Melinda Coleman; Fred Bailleul; Laura Blamey; Stephanie Brodie; Arani Chandrapavan; Jason Hartog; David Maynard; Craig Mundy; Eva Plaganyi; et al. (Oceanography, 2024)
Forecasts of an El Niño in 2023/2024 raised concern among Australian marine stakeholders regarding its potential impacts on marine industries and systems. National level seafood-focused climate briefings were requested by the fisheries sector for the first time, driven by various state and regional level meetings and information requests. To respond to stakeholder needs, six virtual national marine climate briefings were undertaken through the austral 2023/2024 summer, underpinned by new subseasonal to seasonal marine heatwave forecast capabilities. These briefings were developed in collaboration with multiple science organizations and were targeted to industry and management authorities across the Australian seafood sector. As a result, targeted information products, additional regional and sector-specific briefings, and state response plans were developed. Collectively, these briefings were a catalyst for positive and rapid action in policy, management, industry, and research arenas. This experience showed that the combination of seasonal forecasting capability, inter-agency coordination, strong stakeholder engagement, and effective science communication plays a critical role in improving the understanding of, planning for, and responses to extreme events.

Challenges in cybersecurity: Lessons from biological defense systems - Edward Schrom; Ann Kinzig; Stephanie Forrest; Andrea L. Graham; Simon A. Levin; Carl T. Bergstrom; Carlos Castillo-Chavez; James P. Collins; Rob J. de Boer; Adam Doupé; Roya Ensafi; Stuart Feldman; et al. (Mathematical Biosciences, 2023)

Depensation in fish recruitment driven by context-dependent interactions with another predator - Colin Dassow; Greg Sass; Stephanie Shaw; Zachary Feiner; Chelsey Nieman; Stuart Jones (Fisheries Research, 2023)

Evaluation of Nasal Oxygen Administration at Various Flow Rates and Concentrations in Conscious, Standing Adult Horses - Danielle Gordon; Stuart Clark-Price; Stephanie Keating; David J. Schaeffer; Kara M. Lascola (Journal of Equine Veterinary Science, 2023)

Effects of different management strategies on long‐term trends of Australian threatened and near‐threatened mammals - Ayesha I. T. Tulloch; Micha V. Jackson; Elisa Bayraktarov; Alexander R. Carey; Diego F. Correa‐Gomez; Michael Driessen; Ian C. Gynther; Mel Hardie; Katherine Moseby; Liana Joseph; Harriet Preece; Andrés Felipe Suarez‐Castro; et al. (Conservation Biology, 2023)
Monitoring is critical to assess management effectiveness, but broadscale systematic assessments of monitoring to evaluate and improve recovery efforts are lacking. We compiled 1808 time series from 71 threatened and near‐threatened terrestrial and volant mammal species and subspecies in Australia (48% of all threatened mammal taxa) to compare relative trends of populations subject to different management strategies. We adapted the Living Planet Index to develop the Threatened Species Index for Australian Mammals and track aggregate trends for all sampled threatened mammal populations and for small ( 5500 g) from 2000 to 2017. Unmanaged populations (42 taxa) declined by 63% on average; unmanaged small mammals exhibited the greatest declines (96%). Populations of 17 taxa in havens (islands and fenced areas that excluded or eliminated introduced red foxes [ Vulpes vulpes ] and domestic cats [ Felis catus ]) increased by 680%. Outside havens, populations undergoing sustained predator baiting initially declined by 75% but subsequently increased to 47% of their abundance in 2000. At sites where predators were not excluded or baited but other actions (e.g., fire management, introduced herbivore control) occurred, populations of small and medium mammals declined faster, but large mammals declined more slowly, than unmanaged populations. Only 13% of taxa had data for both unmanaged and managed populations; index comparisons for this subset showed that taxa with populations increasing inside havens declined outside havens but taxa with populations subject to predator baiting outside havens declined more slowly than populations with no management and then increased, whereas unmanaged populations continued to decline. More comprehensive and improved monitoring (particularly encompassing poorly represented management actions and taxonomic groups like bats and small mammals) is required to understand whether and where management has worked. Improved implementation of management for threats other than predation is critical to recover Australia's threatened mammals.

Time-varying effects of local weather on behavior and probability of breeding deferral in two Arctic-nesting goose populations - Stephanie A. Cunningham; Toryn L. J. Schafer; Christopher K. Wikle; Jay A. VonBank; Bart M. Ballard; Lei Cao; Stuart Bearhop; Anthony D. Fox; Geoff M. Hilton; Alyn J. Walsh; Larry R. Griffin; Mitch D. Weegman (Oecologia, 2023)
Arctic-nesting geese face energetic challenges during spring migration, including ecological barriers and weather conditions (e.g., precipitation and temperature), which in long-lived species can lead to a trade-off to defer reproduction in favor of greater survival. We used GPS location and acceleration data collected from 35 greater white-fronted geese of the North American midcontinent and Greenland populations at spring migration stopovers, and novel applications of Bayesian dynamic linear models to test daily effects of minimum temperature and precipitation on energy expenditure (i.e., overall dynamic body acceleration, ODBA) and proportion of time spent feeding (PTF), then examined the daily and additive importance of ODBA and PTF on probability of breeding deferral using stochastic antecedent models. We expected distinct responses in behavior and probability of breeding deferral between and within populations due to differences in stopover area availability. Time-varying coefficients of weather conditions were variable between ODBA and PTF, and often did not show consistent patterns among birds, indicating plasticity in how individuals respond to conditions. An increase in antecedent ODBA was associated with a slightly increased probability of deferral in midcontinent geese but not Greenland geese. Probability of deferral decreased with increased PTF in both populations. We did not detect any differentially important time periods. These results suggest either that movements and behavior throughout spring migration do not explain breeding deferral or that ecological linkages between bird decisions during spring and subsequent breeding deferral were different between populations and across migration but occurred at different time scales than those we examined.

Agriculture without paraquat is feasible without loss of productivity—lessons learned from phasing out a highly hazardous herbicide - Alexander M. Stuart; Charles N. Merfield; Finbarr G. Horgan; Sheila Willis; Meriel A. Watts; Fernando Ramírez-Muñoz; Jorge Sánchez U; Leah Utyasheva; Michael Eddleston; Mark L. Davis; Lars Neumeister; Manoé R. Sanou; et al. (Environmental Science and Pollution Research, 2023)
A small proportion of the thousands of pesticides on the market today are associated with a disproportionately high incidence of severe acute pesticide poisoning and suicide. Paraquat stands out as one of the most lethal pesticides in common use, frequently involved in fatal incidents due to suicides or accidental exposure. Even though paraquat has been banned in over 67 countries, it is still widely used in many others, particularly in Asia and Latin America. Based on a literature review and consultations, this paper identifies options for replacing paraquat and distils practical lessons from numerous successes around the world. Our aim is to support regulators, policymakers, agronomists and the supply chain sector with practical information related to phasing out paraquat . Production data consistently failed to show any negative effects of banning paraquat on agricultural productivity. A wide range of alternative approaches to weed management and crop defoliation are available, many of which do not rely on herbicides. Over 1.25 million farmers in low- and middle-income countries (LMICs) successfully produce a range of crops for private voluntary standards (PVS) in food and fiber supply chains which prohibit paraquat use. We conclude from the findings of this study that eliminating paraquat will save lives without reducing agricultural productivity. Less hazardous and more sustainable alternatives exist. To enhance successful adoption and uptake of these methods on a wide scale, farmers require training and support within an enabling policy environment.

Species divergence under competition and shared predation - Marius Roesti; Jeffrey S. Groh; Stephanie A. Blain; Magnus Huss; Peter Rassias; Daniel I. Bolnick; Yoel E. Stuart; Catherine L. Peichel; Dolph Schluter (Ecology Letters, 2023)
Species competing for resources also commonly share predators. While competition often drives divergence between species, the effects of shared predation are less understood. Theoretically, competing prey species could either diverge or evolve in the same direction under shared predation depending on the strength and symmetry of their interactions. We took an empirical approach to this question, comparing antipredator and trophic phenotypes between sympatric and allopatric populations of threespine stickleback and prickly sculpin fish that all live in the presence of a trout predator. We found divergence in antipredator traits between the species: in sympatry, antipredator adaptations were relatively increased in stickleback but decreased in sculpin. Shifts in feeding morphology, diet and habitat use were also divergent but driven primarily by stickleback evolution. Our results suggest that asymmetric ecological character displacement indirectly made stickleback more and sculpin less vulnerable to shared predation, driving divergence of antipredator traits between sympatric species.

How to prioritize species recovery after a megafire - Michelle Ward; Josie Carwardine; James E. M. Watson; Anna Pintor; Stephanie Stuart; Hugh P. Possingham; Jonathan R. Rhodes; Alexander R. Carey; Nancy Auerbach; April Reside; Chuan Ji Yong; Ayesha I. T. Tulloch (Conservation Biology, 2022)
Due to climate change, megafires are increasingly common and have sudden, extensive impacts on many species over vast areas, leaving decision makers uncertain about how best to prioritize recovery. We devised a decision‐support framework to prioritize conservation actions to improve species outcomes immediately after a megafire. Complementary locations are selected to extend recovery actions across all fire‐affected species’ habitats. We applied our method to areas burned in the 2019−2020 Australian megafires and assessed its conservation advantages by comparing our results with outcomes of a site‐richness approach (i.e., identifying areas that cost‐effectively recover the most species in any one location). We found that 290 threatened species were likely severely affected and will require immediate conservation action to prevent population declines and possible extirpation. We identified 179 subregions, mostly in southeastern Australia, that are key locations to extend actions that benefit multiple species. Cost savings were over AU$300 million to reduce 95% of threats across all species. Our complementarity‐based prioritization also spread postfire management actions across a wider proportion of the study area compared with the site‐richness method (43% vs. 37% of the landscape managed, respectively) and put more of each species’ range under management (average 90% vs. 79% of every species’ habitat managed). In addition to wildfire response, our framework can be used to prioritize conservation actions that will best mitigate threats affecting species following other extreme environmental events (e.g., floods and drought).

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Typologies of collaborative governance for scaling nature-based solutions in two strategic South African river systems - Stephanie J. E. Midgley; Karen J. Esler; Petra B. Holden; Alanna J. Rebelo; Sabine I. Stuart-Hill; James D. S. Cullis; Nadine Methner (Ambio, 2021)

New insights into patterns and rates of tooth replacement in serrasalmid and characid fishes, with implications for the subsistence fishery of P eru's remote ribereños villages - Courtney E. Stuart; Stephanie J. Green; Oksana Vernygora; Aaron R. H. LeBlanc; Mary H. Bertschi; Maria Brown (Journal of Fish Biology, 2021)
We explored patterns, rates and unexpected socio‐ecological consequences of tooth replacement in serrasalmids and characids of the Peruvian Amazon using microcomputed tomography. Of 24 specimens collected in February 2019, representing a mix of red‐bellied piranha Pygocentrus nattereri , redeye piranha Serrasalmus rhombeus , silver dollar fish Ctenobrycon hauxwellianus and mojara Astyanax abramis , six individuals possessed edentulous jaw quadrants. On average, 22.9% of fish collected per day from these species featured incomplete dentition, a value three to five times higher than anticipated based on replacement rates estimated from captive fish, differences that may be driven by ontogeny, seasonality or environmental quality.

Analytical and Computational Advances, Opportunities, and Challenges in Marine Organic Biogeochemistry in an Era of “Omics” - Andrew D. Steen; Stephanie Kusch; Hussain A. Abdulla; Nevenka Cakić; Sarah Coffinet; Thorsten Dittmar; James M. Fulton; Valier Galy; Kai-Uwe Hinrichs; Anitra E. Ingalls; Boris P. Koch; Elizabeth Kujawinski; et al. (Frontiers in Marine Science, 2020)

Effects of in vivo exposure to tritium: a multi-biomarker approach using the fathead minnow, Pimephales promelas - Béatrice Gagnaire; Isabelle Gosselin; Amy Festarini; Stephanie Walsh; Isabelle Cavalié; Christelle Adam-Guillermin; Claire Della-Vedova; Francesca Farrow; Sang Bog Kim; Alexi Shkarupin; Hui Qun Chen; Danielle Beaton; et al. (Environmental Science and Pollution Research, 2020)

A toxicity-based analysis of Canada’s National Pollutant Release Inventory (NPRI): a case study in Nova Scotia - Stephanie Taylor; Stuart Johnston Edwards; Tony R. Walker (Environmental Science and Pollution Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Origin of Sedimentary BHPs Along a Mississippi River–Gulf of Mexico Export Transect: Insights From Spatial and Density Distributions - Stephanie Kusch; Julio Sepúlveda; Stuart G. Wakeham (Frontiers in Marine Science, 2019)

Visitor Preferences for Visual Changes in Bark Beetle-Impacted Forest Recreation Settings in the United States and Germany - Arne Arnberger; Martin Ebenberger; Ingrid E. Schneider; Stuart Cottrell; Alexander C. Schlueter; Eick von Ruschkowski; Robert C. Venette; Stephanie A. Snyder; Paul H. Gobster (Environmental Management, 2018)

Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Richard J. Sanders; Stephanie A. Henson; Adrian P. Martin; Tom R. Anderson; Raffaele Bernardello; Peter Enderlein; Sophie Fielding; Sarah L. C. Giering; Manuela Hartmann; Morten Iversen; Samar Khatiwala; Phyllis Lam; et al. (Frontiers in Marine Science, 2016)

Long-term copper partitioning of metal-spiked sediments used in outdoor mesocosms - Stephanie Gardham; Grant C. Hose; Stuart L. Simpson; Chad Jarolimek; Anthony A. Chariton (Environmental Science and Pollution Research, 2014)

Microsatellite loci for genetic analysis of the arctic gadids Boreogadus saida and Arctogadus glacialis - R. John Nelson; Caroline Bouchard; Matias Madsen; Kim Praebel; Eric Rondeau; Kristian von Schalburg; Jong S. Leong; Stuart Jantzen; Zoe Sandwith; Stephanie Puckett; Amber Messmer; Svein-Erik Fevolden; et al. (Conservation Genetics Resources, 2013)

Altered patterns of multiple recombinant events are associated with nondisjunction of chromosome 21 - Tiffany Renee Oliver; Stuart W. Tinker; Emily Graves Allen; Natasha Hollis; Adam E. Locke; Lora J. H. Bean; Reshmi Chowdhury; Ferdouse Begum; Mary Marazita; Vivian Cheung; Eleanor Feingold; Stephanie L. Sherman (Human Genetics, 2012)

Thermochronometric constraints on the tectonic evolution of the Serifos detachment, Aegean Sea, Greece - Stephanie Brichau; Stuart Thomson; Uwe Ring (International Journal of Earth Sciences, 2010)

Reproduction of Echinacea angustifolia in fragmented prairie is pollen‐limited but not pollinator‐limited - Stuart Wagenius; Stephanie Pimm Lyon (Ecology, 2010)
Pollen limitation of plant reproduction occurs in many plant species, particularly those in fragmented habitat; however, causes of pollen limitation are often unknown. We investigated the relationship between pollen limitation and pollinator visitation in the purple coneflower, Echinacea angustifolia (Asteraceae), which grows in the extremely fragmented tallgrass prairie of North America. Previous investigations showed that pollen limitation of E. angustifolia increases with plant isolation and decreases with population size. We observed insect visitation to E. angustifolia over two flowering seasons and estimated pollen limitation of observed plants, using seed set as a proxy measure in 2004 and persistence of receptive style rows in 2005. We analyzed spatial patterns of bee visitation and pollination at two spatial scales: individual isolation, as measured by the distance to their k th nearest flowering neighbors ( k = 1 −15), and population size. Our results indicate that E. angustifolia is pollinated by over 26 species of native bees, with 70–75% of visits by halictid bees. Surprisingly, in both years, bee visitation increased with isolation of individual plants and did not vary significantly with population size. As expected, plant isolation increased pollen limitation and lowered seed set. There was no effect of population size on seed set in 2004, and pollen limitation decreased nonsignificantly with population size in 2005. We conclude that pollen receipt limits reproduction in E. angustifolia, but pollinator visitation does not. Remarkably, isolated plants simultaneously have increased rates of pollinator visitation by pollinators and decreased reproduction. We discuss alternative explanations of pollen limitation that are consistent with this apparent discrepancy, including a decline in the availability of compatible conspecific pollen with increased plant isolation.

Soil drying and nitrogen availability modulate carbon and water exchange over a range of annual precipitation totals and grassland vegetation types - SAMUEL B. St. CLAIR; ERIKA A. SUDDERTH; MARC L. FISCHER; MARGARET S. TORN; STEPHANIE A. STUART; ROHIT SALVE; DENNIS L. EGGETT; DAVID D. ACKERLY (Global Change Biology, 2009)
Increased intensity in precipitation events and longer periods of water deficit are predicted as a general trend under future climate scenarios with potentially large effects on terrestrial ecosystem function. The primary objective of this study was to understand how variation in the intensity of precipitation inputs followed by intermittent soil drying events influence leaf and ecosystem carbon dioxide (CO 2 ) and water exchange in a California annual grassland mesocosm experiment. We further examined how nitrogen (N) availability, and differences in plant community composition (grass‐forb combinations) affected gas exchange responses to the precipitation treatments. Net ecosystem CO 2 exchange (NEE) and evapotranspiration (ET) increased significantly with greater precipitation and were positively correlated with soil moisture. A repeated 10‐day soil drying period, following 11 days of watering, strongly depressed NEE over a range of annual precipitation totals (297, 657 and 987 mm), and plant community types. Ecosystem dark respiration ( R e ) and leaf level photosynthesis ( A max ) showed greater sensitivity to periods of soil drying in the low precipitation plots (297 mm). N additions significantly increased NEE and R e , particularly as water availability was increased. Across the range of precipitation totals and plant community types, intermittent periods of soil moisture deficit and native soil N availability constrained leaf and ecosystem level CO 2 exchange, while the influence on water vapor exchange was less pronounced.

Sequencing EVC and EVC2 identifies mutations in two-thirds of Ellis–van Creveld syndrome patients - Stuart W. J. Tompson; Victor L. Ruiz-Perez; Helen J. Blair; Stephanie Barton; Victoria Navarro; Joanne L. Robson; Michael J. Wright; Judith A. Goodship (Human Genetics, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

A protocol for high-throughput phenotyping, suitable for quantitative trait analysis in mice - Leah C. Solberg; William Valdar; Dominique Gauguier; Graciela Nunez; Amy Taylor; Stephanie Burnett; Carmen Arboledas-Hita; Polinka Hernandez-Pliego; Stuart Davidson; Peter Burns; Shoumo Bhattacharya; Tertius Hough; et al. (Mammalian Genome, 2006)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Ultrasound for the Visualization and Quantification of Tumor Microcirculation - F. Stuart Foster; Peter N. Burns; David H. Simpson; Stephanie R. Wilson; Donald A. Christopher; David E. Goertz (Cancer and Metastasis Reviews, 2000)